FFECT OF OCIMUM SANCTUM DRY LEAF POWDER ON IMMUNE RESPONSE IN BROILERS FED OCHRATOXIN - Nayak, Anju; Joseph, E; Nayak, S; Swamy, M; Baghel, RPS (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted to evaluate the immunomodulatory property of Ocimum Sanctum dry leaf powder in ochratoxin supplemented fed broilers. Day old, 108 broilers were distributed into nine groups in duplicate. Serum was collected on day 15th, 25th and 35th and humoral immunity in broilers towards New castle disease was measured. Significantly lower titer against NDV was observed in broilers receiving ochratoxin, on 15th, 25th and 35th day. Broilers receiving 4 g Ocimum Sanctum dry leaf powder / kg feed showed highest NDV titer followed by broilers receiving 2 g Ocimum Sanctum dry leaf powder / kg feed. Significantly (P<0.05) improved haemagglutination inhibition titer was observed in group fed 4 g Ocimum Sanctum dry leaf powder / kg feed along with 4 ppm ochratoxin on 15th and 35th day in comparison to broilers fed only ochratoxin.